PRELIM - Suhaimy, Khairul Azman (Journal of Techno-Social, 2015)
PATRONAGE,SCIENTIFIC ADVISORY BOARD,EDITORIAL BOARD,ASSOCIATE EDITORS,EDITORIAL MANAGEMENT COMMITTEE,MESSAGE FROM EDITOR IN CHIEF,CONTENTS